Conscious distance monitoring and perceived exertion in light-deprived cycling time trial - Pinheiro, F. A.; Santos, T. M.; Pires, F. O. (Physiology & Behavior, 2016)
The monitoring of distance is crucial to calculate the metabolic requirement and the ratings of perceived exertion (RPE) for a given exercise bout. Visual cues provide valuable information for distance estimation, navigation and orientation. The present study investigated if light deprivation may affect the conscious monitoring of distance, RPE and associative thoughts to exercise (ATE) during a 20-km cycling time trial (TT20 km). Eleven male, endurance cyclists performed two TT20 km in illuminated-control and light-deprived laboratory. They were asked to self-report RPE and ATE when they perceived they had completed each 2 km. Results: The light deprivation resulted in elongated perceived distance at each actual 2 km, rather than in illuminated-control trial (P < 0.05). Although there was no difference in RPE when it was plotted as a function of the perceived distance, RPE was lowered in light-deprived environment when it was plotted as a function of the actual distance (P < 0.05). Additionally, ATE was lowered during TT20 km in light deprivation (P < 0.01); however, pacing and performance were unaffected in light-deprived environment. Conclusion: Results suggest that pacing and performance were regulated through a system which was unaffected in light-deprived environment, despite the altered conscious distance monitoring and perceptive responses.